Sinais de romanização na Torre de Lapela - Monção - Almeida, Carlos A. Brochado de (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The Lapela Tower is the only remaining element of a medieval castle built in the meridional bank of Minho River and dismantled by the end of the 17th and beginning of the 18th century. An archaeological intervention made in the perimeter of the ancient wall discovered the medieval foundation and, beyond it, evidential proofs of roman’s ceramic construction, probably connected with a fanun or caponae.